2016
DOI: 10.3390/s16111930
|View full text |Cite
|
Sign up to set email alerts
|

Approach for Self-Calibrating CO2 Measurements with Linear Membrane-Based Gas Sensors

Abstract: Linear membrane-based gas sensors that can be advantageously applied for the measurement of a single gas component in large heterogeneous systems, e.g., for representative determination of CO2 in the subsurface, can be designed depending on the properties of the observation object. A resulting disadvantage is that the permeation-based sensor response depends on operating conditions, the individual site-adapted sensor geometry, the membrane material, and the target gas component. Therefore, calibration is neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The line sensor presented here covers the entire range of typical CO 2 concentrations in soil with high precision. This was demonstrated for <1.6% CO 2 by Lazik and Ebert (2012) and for concentrations <8% by Lazik and Sood (2016) for dry gases. In this study, we demonstrated the applicability of the line sensor for natural, humid soil conditions.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…The line sensor presented here covers the entire range of typical CO 2 concentrations in soil with high precision. This was demonstrated for <1.6% CO 2 by Lazik and Ebert (2012) and for concentrations <8% by Lazik and Sood (2016) for dry gases. In this study, we demonstrated the applicability of the line sensor for natural, humid soil conditions.…”
Section: Resultsmentioning
confidence: 74%
“…Also, locally incomplete phase equilibrations would result in a reduced mean soil CO 2 concentration. In addition, the measurement uncertainty and bias of the sensors, which was investigated under precisely defined dry‐gas conditions by Lazik and Sood (2016), will have contributed to this 5% difference.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations